2000
DOI: 10.1016/s0306-4522(99)00537-0
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic injury induces differential expression of cell death genes in organotypic brain slice cultures determined by complementary DNA array hybridization

Abstract: Abstract-The expression of a large panel of selected genes hypothesized to play a central role in post-traumatic cell death was shown to be differentially altered in response to a precisely controlled, mechanical injury applied to an organotypic slice culture of the rat brain. Within 48 h of injury, the expression of nerve growth factor messenger RNA was significantly increased whereas the levels of bcl-2, a-subunit of calcium/calmodulin-dependent protein kinase II, cAMP response element binding protein, 65,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 72 publications
0
49
0
Order By: Relevance
“…Recently, Jin et al (2001) reported that neurogenesis in the SVZ was induced after focal ischemia in the rat. In the brain slice culture system, it was reported that a significant amount of neuronal cell death also occurred during culture (Morrison et al, 2000;Okada et al, 1995), resulting in stimulation of neurogenesis (Biebl et al, 2000). These findings suggest that CMV-susceptible immature glial cells, including neural progenitor cells, may proliferate in damaged brains with neural regeneration, such as the brains of AIDS patients.…”
Section: Immature Glial Cells In MCMV Infectionmentioning
confidence: 78%
“…Recently, Jin et al (2001) reported that neurogenesis in the SVZ was induced after focal ischemia in the rat. In the brain slice culture system, it was reported that a significant amount of neuronal cell death also occurred during culture (Morrison et al, 2000;Okada et al, 1995), resulting in stimulation of neurogenesis (Biebl et al, 2000). These findings suggest that CMV-susceptible immature glial cells, including neural progenitor cells, may proliferate in damaged brains with neural regeneration, such as the brains of AIDS patients.…”
Section: Immature Glial Cells In MCMV Infectionmentioning
confidence: 78%
“…Transcription of the first strand of cDNA was performed in situ to increase the yield of cDNA from the endogenous mRNA pool before microdissection (Crino et al, 1996;Morrison et al, 2000). After TUNEL and active caspase 3 immunohistochemistry, sections were incubated overnight with the oligo-dT primer coupled with a T7 RNA polymerase promoter sequence (oligo-dT-T7), as described previously (Eberwine et al, 1992b;Phillips and Eberwine, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…These techniques are restricted to the use of tissue homogenates that prevent the localization of the cellular source of the differential expression. The use of amplified antisense mRNA (aRNA) bypasses these restric-tions by allowing the detection of multiple mRNA species within individual cells in culture or fixed tissues (Eberwine et al, 1992b;Crino et al, 1996;Morrison et al, 2000;O'Dell et al, 2000). Recently, this methodology was used to generate an expression profile of apoptotic cortical cells at two time points after experimental brain injury in the rat (O'Dell et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the presence of acute seizures independently predicts seizure recurrence. Given the rapidity with which injury-induced alterations to physiological and biochemical processes occur in neural circuits (D'Ambrosio and Perucca 2004;Miller et al 1990;Morrison et al 2000;Topolink et al 2003a,b), the plastic changes in cortical function that support epileptogenesis could develop quickly after brain injury. However, in human epidemiologic studies, the role of early seizures is less clear.…”
Section: Introductionmentioning
confidence: 99%